Potential of energy recuperation in the exhaust gas of state of the art light duty vehicles with thermoelectric elements. (15th July 2018) - Durand, Thibaut; Dimopoulos Eggenschwiler, Panayotis; Tang, Yinglu; Liao, Yujun; Landmann, Daniel
Abstract: About 30% of the fuel energy is lost in combustion engines to the exhaust gas. New development of thermoelectric materials allows to partly recuperating the lost heat. New Half-Heusler materials using only low-priced elements show promising performances for heat conversion in the temperature range of a vehicle exhaust. An investigation of the installation of Half-Heusler-based thermoelectric generators at the manifold and after the exhaust after-treatment system (ATS) of 4 light duty vehicles (2 gasolines and 2 diesels) has been made. Gas temperatures at the manifold and after the ATS were simulated based on measured data. These reach 800 °C and 600 °C respectively during a typical driving cycle. During the WLTC, an average of 100 W of electricity can be generated at the manifold and 30 W after the ATS, without adding specific heat transfer enhancing devices in the exhaust pipe. The geometric dimensions of the TEGs must be adapted in order to match the optimal thermal resistance according to their location in the exhaust and the vehicle type (differing heat flows and temperatures) to recuperate an optimal amount of energy.